Research on the Impact of Digital Transformation on Corporate Business Credit in the Context of Double Cycle: Based on the Moderating Effect of Outward Investment - Zhong, Kexin; Ye, Jianmu (Transactions on Social Science, Education and Humanities Research, 2024)
This paper empirically examines the impact of digital transformation on business credit, using data from 2013-2022 as a sample. It also studies the impact of outward investment on the relationship between the two in the context of the double cycle. The study demonstrates that the digital transformation of enterprises has a significant positive impact on the availability of business credit. The effect of digital transformation on improving business credit of enterprises is stronger when the outward investment of the business credit market is in the upward stage. The outbound merger and acquisition mode has a more significant moderating effect on digital transformation and business credit. The analysis of heterogeneity reveals that digital transformation has a more significant enhancement effect on the business credit of non-high-tech industries, non-state-owned enterprises, and enterprises with high equity concentration that are at a financing disadvantage. Additionally, it is found that digital transformation can improve information transparency, reduce agency costs, and alleviate financing constraints, thereby enhancing the level of business credit financing for enterprises. The aforementioned findings offer valuable theoretical references and managerial insights for the implementation of digital transformation in enterprises and research related to outward investment in the context of the double-cycle.